Smart IoT energy optimisation and localisation monitoring for e-bike sharing - Mohamed, Mawada Ahmed; Toha, Siti Fauziah; Rahman, Md Ataur; Khairudin, Moh. (International Islamic University Malaysia-IIUM, 2025)
E-bike sharing has emerged as a sustainable and convenient mode of transportation, offering lightweight, energy-efficient mobility solutions. However, existing systems face challenges such as limited input parameters for modeling, leading to inefficiencies in energy optimization algorithms and power assist mechanisms. A significant concern is the rapid depletion of batteries, which reduces the availability of e-bikes, increases operational costs for fleet managers, and impacts user satisfaction. To address these challenges, this project developed a Smart IoT Energy Optimization and Localization Monitoring System that integrates multi-sensor data, IoT connectivity, and advanced data analytics to monitor real-time usage patterns, battery levels, and the location of e-bikes. The methodology involved integrating sensors to collect key data, implementing connectivity for real-time monitoring, and developing an energy optimization algorithm to prolong battery life, improving the efficiency of the e-bike sharing system. The results demonstrated a 15% improvement in energy efficiency, which increased battery state-of-charge (SOC) and extended operational range. Additionally, the system enabled better fleet management by ensuring optimal energy usage and the availability of e-bikes for users. This approach aligns seamlessly with the Sustainable Development Goals (SDGs) by promoting eco-friendly transportation and enhancing user accessibility. The integration of IoT technology has proven effective in overcoming the limitations of traditional systems, offering a scalable and efficient solution for modern urban mobility.